2019
DOI: 10.3390/rs11182105
|View full text |Cite
|
Sign up to set email alerts
|

Canopy Height and Above-Ground Biomass Retrieval in Tropical Forests Using Multi-Pass X- and C-Band Pol-InSAR Data

Abstract: Globally available high-resolution information about canopy height and AGB is important for carbon accounting. The present study showed that Pol-InSAR data from TS-X and RS-2 could be used together with field inventories and high-resolution data such as drone or LiDAR data to support the carbon accounting in the context of REDD+ (Reducing Emissions from Deforestation and Forest Degradation) projects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…Linear regression between the lidar-based and PolInSAR-model-based vegetation height for the temperate and tropical forest showed a 0.89 coefficient of determination with 2.3 m RMSE and a 0.98 coefficient of determination with 2.1 m RMSE [81]. Several other studies were also conducted in which highly accurate results were reported by the researchers [68,[82][83][84][85].…”
Section: Discussionmentioning
confidence: 82%
“…Linear regression between the lidar-based and PolInSAR-model-based vegetation height for the temperate and tropical forest showed a 0.89 coefficient of determination with 2.3 m RMSE and a 0.98 coefficient of determination with 2.1 m RMSE [81]. Several other studies were also conducted in which highly accurate results were reported by the researchers [68,[82][83][84][85].…”
Section: Discussionmentioning
confidence: 82%
“…InSAR techniques have not been extensively applied to tropical regions, although a few recent examples exist [40,41]. One study achieved an R 2 equal to 0.54 to 0.69 and an RMSE of 4.65 to 8.44 m at 3 to 12 m over tropical forest [40].…”
Section: Estimating Forest Stand Height With Remote Sensingmentioning
confidence: 99%
“…InSAR techniques have not been extensively applied to tropical regions, although a few recent examples exist [40,41]. One study achieved an R 2 equal to 0.54 to 0.69 and an RMSE of 4.65 to 8.44 m at 3 to 12 m over tropical forest [40]. However, it is essential to prioritize the investigation of methods taking advantage of data that are openly accessible when considering the needs of end users.…”
Section: Estimating Forest Stand Height With Remote Sensingmentioning
confidence: 99%
“…In [1,2], methods were developed for determining above-ground biomass, the first being based on water cloud modelling (WCM) from quad-polarised L-band (PALSAR) data on the Advanced Land Observing Satellite-2 (ALOS-2), and the second from dual-polarised X-band TerraSAR-X and quad-pol-InSAR C-band data from RADARSAT-2 data. The concept of water cloud modelling (WCM) was developed in [3], in which a vegetation canopy was represented by a water cloud, based on a number of parameters which were obtained through regression analysis of the radar cross section data for ground truth data based on four crop types.…”
Section: Overview Of Contributionsmentioning
confidence: 99%
“…In [2], the authors determined canopy height and above-ground biomass in a peat swamp tropical forest, with an area of 4340 ha, in central Kalimantan, on the island of Borneo, Indonesia, using pol-InSAR data. Airborne lidar data, with a point spacing of 10.7 points/m 2 and drone photography with a ground sampling distance of 5 cm, were derived over all field inventory areas, where DBH, tree height, and species of sample trees were determined.…”
Section: Overview Of Contributionsmentioning
confidence: 99%